To substitute the value of y from the first equation into the second equation, we replace y with (-x-4). The second equation becomes:
3x + (-x-4) = 8
Simplifying this equation further, we get:
2x - 4 = 8
Adding 4 to both sides of the equation, we have:
2x = 12
Dividing both sides of the equation by 2, we find:
x = 6
Therefore, the correct answer is x=6.
From the following system of equations, create a new equation by substituting the value of y from the first equation into the second equation.
From the new equation, evaluate the value of x.
y=−x−4
3x+y=8
Choose the correct option
(1 point)
Responses
x=6
x=6
x=8
x=8
x=3
x=3
x=12
3 answers
is this correct
Yes, that is correct. My previous response contains the correct steps to solve the given system of equations and evaluate the value of x as x=6.